A ground book on engineering mathematics(Volume-II(A)) - Mukherjee, Arup Kumar (Shreedhar Prakashani, 2020)
A ground book on engineering mathematics(Volume-II(A)) / Mukherjee, Arup Kumar. -- Kolkata: Shreedhar Prakashani, 2020 510 M954e2V2A 2nd ed. No. of Copies : 2